Cat's Cradle - "Daniel, Lucy" (Hodder Children's: London, 1999)
Mandy and James are taking part in their school nativity play, which their teacher, Miss Oswald, is organising. Miss Oswald tells them she's found a little kitten in her garage. Though she loves animals, she's so busy at work that she doesn't feel it would be fair to keep it. Can Mandy persuade her teacher to change her mind?
Keywords: Animal Ark